캄필로박터 종에 대한 항체 - PERRUZZA LISA; GRASSI FABIO; PIZZUTO MATTEO; BENIGNI FABIO; CORTI DAVIDE (2021)
본 개시내용은 캄필로박터에 특이적이고, 특정 실시형태에서 대상체에서 캄필로박터 감염을 중화시킬 수 있는 항체 및 이의 항원 결합 단편을 제공한다. 특정 실시형태에서, 항체 또는 항원 결합 단편은 IgA 항체, 예컨대, 예를 들어, 분비성 IgA 항체을 포함한다. 또한 개시된 항체 또는 항원 결합 단편을 포함하는 약제학적 조성물이 제공된다. 대상체에서 캄필로박터 감염을 치료 또는 예방하기 위해 항체, 항원 결합 단편, 및 조성물을 사용하는 방법이 또한 제공된다. 특정 실시형태에서, 본 개시내용의 재조합 분비성 IgA 항체는 캄필로박터 감염되었거나 감염 위험이 있는 대상체에 경구 투여된다. The instant disclosure provides antibodies and antigen-binding fragments thereof that are specific for Campylobacter and, in certain embodiments, are capable of neutralizing a Campylobacter infection in a subject. In certain embodiments, the antibody or antigen binding fragment comprises an IgA antibody, such as, for example, a secretory IgA antibody. Also provided are pharmaceutical compositions comprising a disclosed antibody or antigen-binding fragment. Methods of using the antibodies, antigen-binding fragments, and compositions to treat or prevent a Campylobacter infection in a subject are also provided. In certain embodiments, recombinant secretory IgA antibodies of the instant disclosure are administered orally to a subject having or at risk of developing a Campylobacter infection.